Literature review of location-based mobile games in education: challenges, impacts and opportunities - Ribeiro, Fernando Reinaldo (2021)
With the universal use of mobile computing devices, there has been a notable increasein the number of mobile applications developed for educational purposes. Gamification strategiesoffer a new set of tools to educators and, combined with the location services provided by thosedevices, allow the creation of innovative location-based mobile learning experiences. In this literaturereview, we conduct an analysis of educational mobile location-based games. The review includesarticles published from January of 2010 to October of 2020, and from 127 records screened, 26 articleswere analysed in full-text form. This analysis allowed us to answer the following six predefinedresearch questions: Who are the target audiences for location-based games? In which subjects arelocation-based games most used? Which strategies are implemented with mobile devices to improvethe student’s learning process? What are the main impacts of location-based games on students’learning? What are the main challenges to the development of location-based games for education?What future tendencies and research opportunities can be identified from the analysis of the currentstate of the art?